THE USAGE OF MS WORD AND JAVASCRIPT IN E-LEARNING COURSEWARE DEVELOPMENT: Received: 06th May 2021; Revised: 20th July 2021, 20th September 2021, 30th December 2021; Accepted: 31st December 2021 - Lee, Diana Phooi Yan; Chai, Teck Jung (PUPIL: International Journal of Teaching, Education and Learning, 2022)
This paper introduces a new approach that enables a simplified and automated development of interesting and attractive e-learning courseware by using a Java template. This new approach enables the development of better-quality e-learning courseware in less time and at less cost, and without pre-requisite knowledge of complicated software such as Macromedia, FrontPage, and etc. In the development process, Microsoft Word, HTML coding, and JavaScript are used. In this e-learning courseware development, Microsoft Word software is used for content editing and saved as a .html file. The saved .html file will be encoded using JavaScript for the files to be viewed on web browsers such as Internet Explorer or Chrome. Developing, editing and updating are made simple as the developers only need to amend the.doc file through Microsoft Word and save it as a .html file. The JavaScript will automatically generate the link between the .doc and .html files. This approach has been tested by selected polytechnic lecturers and received positive feedback. The developed e-learning courseware was somehow limited to the functions and features provided by MS Word Software. Therefore, for future study, developers may apply other applications such as Kahoot, Quizizz, etc to make the learning process more engaging and interesting. Overall, this is a user-friendly tool for people or subject matter experts who would like to develop rapid and simple e-learning courseware.